DNA METHYLATION AND FESOD GENE EXPRESSION AFFECTED BY PLANT DENSITY IN ZEA MAYS L. - & Alfalahi, Shenawa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Methylation Sensitive Amplification Polymorphism (MSAP) was used to characterize the alterations in DNA methylation in maize (Zea mays L.) inbred lines and their half-daillels affected by plant densities (213333 plant h-1 and 13333 plant h-1). The two restriction was enzymes ( HpaII and MspI) succeeded in diagnosing a total of 23 specific loci, most of (22 loci) were Methylation Sensitive Loci (MSL), while the only one NML (No Methylated Loci) was monomorphic. Thirteen out of 22 MSL loci polymorphic, recording a were polymorphism percentage of 59%. Results of FeSOD gene expression cleared the different response of maize inbreds and hybrids to high plant density stress. Generally, the expression of  the targeted gene was increased in plants submitted to high plant density stress compared with low density. The inbred 3 and its single hybrid 1×3 achieved the highest level of gene expression under high planting density (5505.7 and 21098.6 copy, respectively), meanwhile, inbred 5 and it's single hybrid 4×5 gained the maximum level of FeSOD expression at the low plant density (8317.6 and 6862.1 copy, respectively). The response reached to its maximum limit in many of those genotypes, some other genotypes showed relatively steady performance along with higher stress, such as parent 1, that gave the lowest number of gene copies in both, high and low plant density (1375.8 and 1569.5 copy, respectively).